Liquid milk: Cash constraints and day-to-day intertemporal choice in financial diaries - Geng, Xin; Janssens, Wendy; Kramer, Berber (International Food Policy Research Institute, 2017)
This paper analyzes implications of cash constraints for collective marketing, using the case of the Kenyan dairy sector. Collective marketing, for instance through cooperatives, can improve smallholder farmer income but relies on informal, nonenforceable agreements to sell outputs collectively. Side selling of output in the local market occurs frequently and is typically attributed to price differences between the market and cooperative. This paper provides an alternative explanation, namely that farmers sell in the local market when they are cash constrained because cooperatives defer payments while buyers in local markets pay cash immediately. Building on semiparametric estimation techniques for panel data, we find robust evidence of this theory. High-frequency, high-detail panel data show that farmers sell more in the local market, in particular to buyers who pay cash immediately, in weeks when they have low cash on hand. Moreover, households cope with health shocks by selling more milk in the local market and less to the cooperative, but only in weeks when they are not covered by health insurance. Increased flexibility in payment and the provision of insurance through agricultural cooperatives can potentially reduce side selling and improve the performance of collective marketing arrangements.